2009
DOI: 10.1021/am9003914
|View full text |Cite
|
Sign up to set email alerts
|

Solution-Prepared Hybrid-Nanoparticle Dielectrics for High-Performance Low-Voltage Organic Thin-Film Transistors

Abstract: Oleic acid capped barium strontium titanate (OA-BST) nanoparticles were synthesized for solution-prepared dielectrics in organic thin-film transistors (OTFTs). The as-synthesized nanoparticles were well-dispersed in organic solvents to deposit very homogeneous dielectric films by direct spin coating. Bottom-gate pentacene TFTs fabricated using these nanoparticle dielectric films showed high mobilities of 1-2 cm(2) V(-1) s(-1) with on/off ratios of 10(3) under a low driven voltage of -2.5 V. Top-gate poly(3,3''… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 53 publications
(73 reference statements)
0
20
0
Order By: Relevance
“…Solution processable dielectric materials e.g. cross‐linked polyvinylphenol and poly(styrene‐block‐ethylene oxide‐block‐styrene) have been applied in printed device fabrications 71–73. However, these dielectrics may not be as effective as vacuum‐deposited HfO 2 and partial alignment reported here offers another route towards achieving high performance FETs.…”
Section: Resultsmentioning
confidence: 99%
“…Solution processable dielectric materials e.g. cross‐linked polyvinylphenol and poly(styrene‐block‐ethylene oxide‐block‐styrene) have been applied in printed device fabrications 71–73. However, these dielectrics may not be as effective as vacuum‐deposited HfO 2 and partial alignment reported here offers another route towards achieving high performance FETs.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, based on the FT-IR and O 1s PES results, it can be concluded that pristine polymer films undergo surface absorption of moisture, and that the increased number of hydroxyl groups present increases charge trapping. [27,28] The binding energies of O 1s photoelectrons in O-Pb and O-H bonds have been reported as 529.5 eV and 531 eV, respectively. [29,30] In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the processing of UV‐absorbing or photoactive metal oxide materials for cosmetic or bio‐oriented applications under neutral pH conditions would be essential to enable applications in life‐science products or pharmaceutics . Classical thin‐film engineering approaches with focus on sustainable methods with nontoxic materials and solvents as can be found in the fabrication of photovoltaics, transistor devices, and water soluble transient electronics applications . Solution processing of metal oxide nanoparticles (NPs) often involves the use of surfactants in order to inhibit particle growth and aggregation.…”
Section: Summary Of Film Properties and Electrical Characteristics Ofmentioning
confidence: 99%
“…Solution processing of metal oxide nanoparticles (NPs) often involves the use of surfactants in order to inhibit particle growth and aggregation. Due to the amphiphilic nature of these surfactants the nanoparticle surface is typically rendered highly hydrophobic, which challenges the use of environmentally desirable solvents such as water and lower alcohols …”
Section: Summary Of Film Properties and Electrical Characteristics Ofmentioning
confidence: 99%